2019
DOI: 10.1371/journal.pntd.0007185
|View full text |Cite
|
Sign up to set email alerts
|

Ebola virus disease-related stigma among survivors declined in Liberia over an 18-month, post-outbreak period: An observational cohort study

Abstract: BackgroundWhile qualitative assessments of Ebola virus disease (EVD)-related stigma have been undertaken among survivors and the general public, quantitative tools and assessment targeting survivors have been lacking.Methods and findingsBeginning in June 2015, EVD survivors from seven Liberian counties, where most of the country’s EVD cases occurred, were eligible to enroll in a longitudinal cohort. Seven stigma questions were adapted from the People Living with HIV Stigma Index and asked to EVD survivors over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 24 publications
2
38
1
1
Order By: Relevance
“…This is the first nationally representative study to determine the prevalence of stigma, its sociodemographic correlates and association with informal and nonintegrated forms of health care such as T&CM use among EVD survivors in Sierra Leone. One key finding from our study is that EVD survivors report high levels of internalised and enacted stigma since discharge from an Ebola treatment centre which is in line with findings from a longitudinal Liberian study that reported high levels of stigma at baseline but lower levels at subsequent follow-up visits [21,23]. Our finding also resonates with similar short term and smaller sample size cross-sectional studies in Sierra Leone [24,25,48], Liberia [20], Guinea [49], and DR Congo [19,40],which reported that EVD survivors experience several forms of internalised and enacted stigma.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is the first nationally representative study to determine the prevalence of stigma, its sociodemographic correlates and association with informal and nonintegrated forms of health care such as T&CM use among EVD survivors in Sierra Leone. One key finding from our study is that EVD survivors report high levels of internalised and enacted stigma since discharge from an Ebola treatment centre which is in line with findings from a longitudinal Liberian study that reported high levels of stigma at baseline but lower levels at subsequent follow-up visits [21,23]. Our finding also resonates with similar short term and smaller sample size cross-sectional studies in Sierra Leone [24,25,48], Liberia [20], Guinea [49], and DR Congo [19,40],which reported that EVD survivors experience several forms of internalised and enacted stigma.…”
Section: Discussionsupporting
confidence: 88%
“…EVD-related stigma has been reported by EVD survivors and their communities in DR Congo (35%), Guinea (26%) and Liberia (3%) [18][19][20], and may be more common among female rather than male EVD survivors [12]. Other factors, which have been reported as predictors of EVD-related stigma, are age, level of education, and having accessed medical care [21]. Liberian research also suggests EVD survivors are reported to be more likely to experience stigma compared to their close contacts who were not infected with EVD virus [22] however the degree of EVD-related stigma may decline among survivors over time [21,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 3,385 individuals studied, 223 (6.6%) were found to have some degree of HL using audiometric evaluation and survey instruments. 19,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Only one of 21 articles used audiometry to objectively measure HL. This study, by Rowe et al, 19 recruited convalescent Ebola survivors and household contacts following the conclusion of the 1995 Ebola outbreak in Kikwit, DRC.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the previous study on Ebola virus disease-related stigma in Liberia, a prevalence of 63.0% [11] was used and the margin of error was set at 5%. Factoring non-response rate of 10%, a minimum sample size of 394 was arrived at.…”
Section: Sample Size and Sampling Techniquementioning
confidence: 99%